Planck early results. VI. The High Frequency Instrument data processing - Planck HFI Core Team; Ade, P. A. R.; Aghanim, N.; Ansari, R.; Arnaud, M.; Ashdown, M.; Aumont, J.; Banday, A. J.; Bartelmann, M.; Bartlett, J. G.; Battaner, E.; Benabed, K.; et al. (\aap, 2011)
n/a
Keywords: cosmic background radiation; cosmology: observations; methods: data analysis; surveys